Modeling The Habitat Suitability Of Javan Banteng (Bos javanicus javanicus) Using Geographic Information System In Ujung Kulon National Park - Handayani , Handayani; Solihin, Dedy Duryadi; Alikodra, Hadi Sukadi; Jakaria, Jakaria; Rianti, Puji; Mahmud, Rois (BIOEDUSCIENCE, 2023)
Background: The Banteng population in Ujung Kulon National Park (TNUK) is less than 500 individuals. The habitat of Java Banteng in conservation areas has largely decreased. One approach to assessing the current status of biodiversity at all levels, especially in endangered species, is to use geospatial technology such as remote sensing and geographic information systems combined with spatial data science. This study aims to create a spatial model of the suitability of the Javan Banteng habitat in the TNUK area and identify the use of the Java Banteng habitat and environmental variables that affect the presence of Javan Banteng. Methods: This research data was collected through coordinate data for stool sampling and data from BTNUK using a method called maximum entropy (maximum). The analysis used the Relative Use Index, Maximum Entropy modeling, and Relative Abundance Index. Results: Based on research, the use of habitat by Java Banteng with the value of making a spatial distribution model can be analyzed by analyzing the contribution of environmental variables based on the level of contribution in percent and the results of the jackknife test, namely the percentage of contribution of environmental variables in this study showed that environmental parameters, slope (37.6%) were the highest parameters, followed elevation (25.8%), land cover (25.3%), and NDVI (6%),  rivers (5.3%). The analysis of five environmental variables used in making the Javan Banteng distribution model showed that at an altitude of 45 meters above sea level, Java Banteng preferred to show 95%. The graph decreased at an altitude above 45 mdpl, and Java Banteng at 200 meters above sea level looked at 0%. Conclusions: Javan Banteng do not like or do not choose places with altitudes ranging from 200 - 625 meters above sea level.